Capital Inflows and Domestic Credit Growth: Empirical Evidence from Emerging Market and Developing Economies - Poch, Kongchheng; Gan, Christopher; Hu, Baiding (Review of Economic Analysis)

(untitled) (International Centre for Economic Analysis, 2023)
This study investigates the extent to which capital inflows and their composition affect domestic credit growth in emerging market and developing economies (EMDEs) and the role of institutional quality in mediating the capital inflows and domestic credit growth nexus. Using a sample of 130 EMDEs from 1991-2015, the study uses generalized method of moments to control for endogeneity issues. The study makes notable contributions to the literature and policy discourse. First, this is the first empirical studies that documents the persistence of domestic credit growth in EMDEs. Second, the study provides a granular analysis of the capital inflows – domestic credit growth nexus. Whereas gross capital inflows significantly exert a positive impact on domestic credit growth, disaggregated-level analyses showed that only foreign direct investment positively affects domestic credit growth whereas portfolio equity has a negative effect; and portfolio debt and other investment do not. Third, the study adds novel evidence that institutional quality plays a crucial role in mediating the capital inflows – domestic credit growth nexus. Fourth, this study crystallises the lens used to investigate the interactions between capital inflows and institutional quality in analysing the capital inflows – domestic credit growth nexus. Finally, the findings are helpful for designing and implementing macro-financial policy and strengthening institutions, especially in managing capital flows and financial sector.